2012
DOI: 10.1098/rspb.2011.2342
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent payoffs and sequential decision-making favour consistent tactic use

Abstract: Although natural selection should have favoured individuals capable of adjusting the weight they give to personal and social information according to circumstances, individuals generally differ consistently in their individual weighting of both types of information. Such individual differences are correlated with personality traits, suggesting that personality could directly affect individuals' ability to collect personal or social information. Alternatively, the link between personality and information use co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
2
24
1
Order By: Relevance
“…In their simulations first arrivals tended to implement the producer strategy and later arrivals were more prone to scrounge, and these behavioral strategies persisted in the individuals' further choices. Our results do not coincide with the theory of Dubois et al [29] because arrival order did not affect social information use pattern in the experiment. However, in support for arrival order theory Seppänen and Forsman [8] showed in a two-species system that first arriving flycatchers use personal information and/or choose randomly in the selection of nest-site features, while about 75% (more than in our intraspecific study) of the late arriving birds relied on the manipulated apparent choices of resident heterospecifics, the tits, even though the number of earlier breeding tit tutors was about the same for all flycatchers.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In their simulations first arrivals tended to implement the producer strategy and later arrivals were more prone to scrounge, and these behavioral strategies persisted in the individuals' further choices. Our results do not coincide with the theory of Dubois et al [29] because arrival order did not affect social information use pattern in the experiment. However, in support for arrival order theory Seppänen and Forsman [8] showed in a two-species system that first arriving flycatchers use personal information and/or choose randomly in the selection of nest-site features, while about 75% (more than in our intraspecific study) of the late arriving birds relied on the manipulated apparent choices of resident heterospecifics, the tits, even though the number of earlier breeding tit tutors was about the same for all flycatchers.…”
Section: Discussioncontrasting
confidence: 99%
“…In some cases the correlation between behavioral strategy and social information use might be a by-product of another process. A recent study demonstrated with mathematical models [29] that division into behavioral roles in a producer-scrounger game can be simply the result of a sequential arrival. Arrival order can drive individuals to consistent roles in the use of social information.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individuals show differences in their impulsiveness or exploratory tendencies as well as a whole slew of other behaviours that have been considered under the theme of animal personalities (R eale & Dingemanse, 2012). What consequences might individual differences have on PS outcomes (Dubois, Giraldeau, & R eale, 2012)? These are all examples where the agent-based linear operator model, unlike evolutionary game-theoretic models, can be used to explore the consequences for social foraging.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although negative frequency-dependent mechanisms may contribute to social niche specialization, they do not always lead to consistent individual differences in behaviour. For example, individuals could specialize in a different social role or behaviour at each time unit, thus maintaining BIC but without leading to any consistency in such differences [8,34]. By contrast, among socially foraging sheep, bold individuals contribute consistently more to group fission events [35].…”
Section: (B) Frequency Dependencementioning
confidence: 99%